Pengaruh Pendidikan Kesehatan dengan Media Video terhadap Pengetahuan Masyarakat tentang Pencegahan Penularan Covid-19 - Wahidah, Alfiatun; Saputra, Bayu; Indra, Rani Lisa (LPPM Hang Tuah Pekanbaru, 2024)
COVID-19 was a global problem with the total number of cases found increasing every day. One of the actions to stop the increase in COVID-19 is the 5M effort (wearing masks, washing hands, maintaining distance, avoiding crowds, and reducing mobility) through education using video tools. The purpose of this research is to find out about changes in education using tools for public insight into preventing the spread of COVID-19 at the Sidomulyo Inpatient Health Center Pekanbaru. This type of research is quantitative, using the pre-experimental design method, one group pretest-posttest, and using a statistical analysis test depending on the sample t-test with 35 samples using Nonprobability Sampling. This study shows the characteristics of respondents with female gender totaling 29 (82.9%), high school education level amounting to 22 (62.9%), and housewife occupation amounting to 16 (45.7%). The results of this study obtained the mean pre-test (8.63) and the mean post-test (15.20) P value 0.000 <0.05, indicating that there is an effect of health education using video tools on public knowledge regarding the prevention of COVID-19 transmission. Health services should make health education an intervention to increase public knowledge.